An Energy Efficient Cluster Based Group Key Management Scheme using Elliptical Curve Cryptography in Wireless Sensor Network - Robinchandra Singh, Usham; Roy, Sudipta (International Journal of Engineering and Technology, 2018)
Group communication with secure authentication in wireless sensor network can be attained by public key cryptography. Security is a measure concern in WSN. Deployment of many key during cluster formation is a important task for secure group communication. To realize this concept, we proposed an energy efficiency group key management using cluster head formation. In existing energy based cluster head selection, each node select cluster head to its neighbors. This paper presents fuzzy logic rules to select cluster head based on the energy cost, node mobility, received signal strength, residual energy model, number of neighbors, and distance of the nodes from the base station. Cluster head take the role of key manager. Moreover, selection of cluster head saves the energy of each node due to lightweight framework and easy authentication can be achieved. This group key is generated by the cluster head and communicated to other members through a secure channel that uses public key cryptography. Due to the resource constraints of wireless sensors, ECC based hierarchical cluster key management scheme is proposed for its small size of keys with same security level with compare to RSA. The technique proposed in this work uses digital signature scheme and encryption-decryption mechanisms using elliptic curve cryptography (ECC). The result shows that the proposed work is faster than other work.Â Â Â